PENGARUH METODE PEMBELAJARAN TIKRAR TERHADAP KEMAMPUAN MENGHAFAL PESERTA DIDIK PADA MATA PELAJARAN TAHFIDZ QUR???AN MA TARBIYAH ISLAMIYAH KOTA TANGERANG - Rosikhotul Baroroh; Ahmad Haromaini; Muhammad Asep Rahmatullah (Universitas Islam Syekh-Yusuf, 2023)
This research was conducted at MA Tarbiyah Islamiyah Tangerang City, research which aims to determine and describe whether or not there is an influence of the tikrar learning method on students' ability to memorize students in the tahfidz Qur'an subject at MA Tarbiyah Islamiyah Tangerang City. With a total sample of 100 samples from 134 populations of class X and XI. Using a descriptive approach and sampling techniques using random sampling. This research instrument uses a questionnaire where for variable X there are 15 statement items and for variable Y there are 15 statement items each. Based on the test results, it was found that there was an influence of the tikrar learning method on students' ability to memorize, as evidenced by the calculation of the coefficient of determination of 31.73%, which means that there was an influence of the tikrar learning method on students' ability to memorize the Qur'an tahfidz subject at MA Tarbiyah Islamiyah Kota Tangerang. By proving that t calculated is greater than t table (6.709 ??? 1.98447). Keywords: Method, Tikrar, Memorizing, Al-Qur'an